Birth weight reduction associated with residence near a hazardous waste landfill. - Berry, M (1997)
We examined the relationship between birth weight and mother's residence near a hazardous waste landfill. Twenty-five years of birth certificates (1961-1985) were collected for four towns. Births were grouped into five 5-year periods corresponding to hypothesized exposure periods (1971-1975 having the greatest potential for exposure). From 1971 to 1975, term births (37-44 weeks gestation) to parents living closest to the landfill (Area 1A) had a statistically significant lower average birth weight (192 g) and a statistically significant higher proportion of low birth weight [odds ratio (OR) = 5.1; 95% confidence interval (CI), 2.1-12.3] than the control population. Average term birth weights in Area 1A rebounded by about 332 g after 1975. Parallel results were found for all births (gestational age > 27 weeks) in Area 1A during 1971-1975. Area 1A infants had twice the risk of prematurity (OR = 2.1; 95 CI, 1.0-4.4) during 1971-1975 compared to the control group. The results indicate a significant impact to infants born to residents living near the landfill during the period postulated as having the greatest potential for exposure. The magnitude of the effect is in the range of birth weight reduction due to cigarette smoking during pregnancy.